Loveology : God, love, marriage, sex, and the never-ending story of male and female - Comer, John Mark, 1980- (Zondervan, 2013)
Presents a biblical view of male-female relationships, revealing what the Scriptures have to say about love, sexuality, romance, and marriage, and answers the most frequently asked questions about sexuality and relationships.